2015
DOI: 10.1007/s11606-015-3356-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Training in a Primary Care Internal Medicine Residency Associated with a Career in Primary Care Medicine?

Abstract: PURPOSE: Professional and governmental organizations recommend an ideal US physician workforce composed of at least 40 % primary care physicians. They also support primary care residencies to promote careers in primary care. Our study examines the relationship between graduation from a primary care or categorical internal medicine residency program and subsequent career choice. METHODS: We conducted a cross-sectional electronic survey of a cohort of internal medicine residency alumni who graduated between 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Several recent studies have identified the importance of culture, [42][43][44][45] providing more evidence that medical training can contribute to trainees' disinterest in primary care. 43,46,47 Additionally, the structure of medical education continues to emphasize specialty medicine while the content and rewards of primary care are all to frequently overlooked. 20 Some respondents offered examples of positive support for navigating the hostile structure and culture of medical school, pointing to possible responses to the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have identified the importance of culture, [42][43][44][45] providing more evidence that medical training can contribute to trainees' disinterest in primary care. 43,46,47 Additionally, the structure of medical education continues to emphasize specialty medicine while the content and rewards of primary care are all to frequently overlooked. 20 Some respondents offered examples of positive support for navigating the hostile structure and culture of medical school, pointing to possible responses to the problem.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recent evidence has found that the quality of continuity clinic experience is related to internal medicine resident satisfaction, 9 and that training models with blocks of protected outpatient time that are separate from inpatient responsibilities may also increase resident satisfaction with their primary care rotations. 10 In addition, the outpatient clinic experiences of residents may be associated with retained interest in primary care careers, 11 though the influence of various factors may also differ by year of training and may be influenced by other experiences prior to residency. 12,13 However, these studies have focused on specific factors, such as residency training satisfaction, and there is a need to understand holistically how the diverse experiences of trainees impact the decision to pursue primary care or another Electronic supplementary material The online version of this article (doi:10.1007/s11606-016-3825-9) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Currently ongoing international studies show that, in spite of positive educational benefits, even elaborately designed and realised curricular interventions have less influence upon the choice of medical specialty and the location of a practice than personal “practical experiences” [16], [17]. Accordingly, mentors are an indispensable part of similar projects [7], [8] and are particularly recommended for sitting in on lectures in the early phases of study, for which both students and mentors must however be prepared [6], [18], [19].…”
Section: Discussionmentioning
confidence: 99%